The Internalization of Entrepreneurial Characters in Pondok Pesantren Anwarus Sholihin Purwokerto - Munjin, Munjin (DINIKA : Academic Journal of Islamic Studies, 2021)
The article is a research on entrepreneur-based pesantren(Islamic boarding school). The two main questions proposed in this article include; what characters have the students been accustomed to and how to internalize those characters to the students? So far, pesantrenhas been stereotyped as an institution that creates unemployment. The society considers pesantrengraduates as competent, and even prominent, in socio-religious field but are lacking in the creative economy field and the utilization of natural resources. PesantrenAnwarus Sholihin Purwokerto, in this context, were striving to bridge the competency gap. This research found that PesantrenAnwarus Sholihin Purwokerto has internalized entrepreneurial character through education and training, entrepreneurship motivation, and practices in production and marketing. Processed food products, including fruits and vegetables, were made from plants harvested in the farm. Along with these activities, pesantreninstilled the entrepreneurship characters to the students, including honesty, self-motivation, teamwork, risk-taking, and creative-innovative skill. Entrepreneur-based pesantren can provide both material and moral contribution to the society. Apart from being economically independent to support the students’ needs, pesantrencan also create entrepreneurial characters that will make the students proud of being its graduates, and in turn, help them becomepersistent individuals in the future.